A Comparison of the Physical Home Food Environments Among Healthy Weight, Overweight, Obese, and Post-Bariatric Surgery Mothers Using an Open Home Food Inventory (P04-152-19) - Rex, Samantha (Curr Dev Nutr, 2019)
OBJECTIVES: The primary aim of this cross-sectional study was to determine if the physical home food environment (availability of foods and beverages in the home) differed by maternal weight status using an open home food inventory. METHODS: Each weight status group (normal weight, overweight, obese, post-bariatric surgery) included eight mothers for a total of 32 mothers (41.5 ± 5.7 years old, 65.6% white) with a child 6–12 years old (9.2 ± 2.3 years old, 65.6% white). An open home food inventory was conducted by research personnel to record all food and beverage items in each home food environment. The item name/brand, size, and quantity was recorded. For each household, all items were entered into Nutrition Data Systems for Research (NDS-R) to determine total energy (kcals) and servings of fruits, vegetables, sugar-sweetened beverages (SSBs), and snacks available in the home. Descriptive statistics were used to analyze demographic characteristics between groups. A one-way ANOVA was used to analyze differences between groups for the following dependent variables: calories, servings of fruits, servings of vegetables, servings of snacks, and servings of SSBs. If there were significant differences post-hoc analyses were conducted. RESULTS: Households had an average of 4.5 ± 1.4 members, and the majority (40.6%) reported an annual income of $100,000 or more. There was a significant difference for SSBs (F (3,28) = 4.06; P = 0.016) in the home food environment with mothers in the post-bariatric group having significantly fewer servings of SSBs available in the home compared to mothers in the obese group (post-bariatric: 35.3 ± 37.3 servings; obese: 158.5 ± 105.7 servings; P = 0.013 ). Total energy (P = 0.27), servings of fruit (P = 0.11), servings of vegetables (0.17), and servings of snacks (P = 0.42) did not significantly differ between households. CONCLUSIONS: Given the recommendation to eliminate SSBs following bariatric surgery these data support that this change is being made within the home food environment of mothers who received bariatric surgery as compared to mothers with obesity. Limited differences between physical home food environments may warrant consideration of additional environmental and behavioral factors associated with weight outcomes. FUNDING SOURCES: S. Robson start-up funds (University of Delaware); I. Kahete was supported by The Delaware INBRE program.